BUDAYA LITERASI DI KALANGAN MAHASISWA FBS UNY - Sari, Esti Swatika; Pujiono, Setyawan (LITERA, 2017)
AbstractThis study aims to describe forms of literacy culture and constraints faced by students in carrying out activities in literacy culture. The research subjects were students of Facultyof Languages and Arts, Yogyakarta State University. The data were collected throughobservations, questionnaires, interviews, and documentation. Theye were analyzed bythe qualitative descriptive technique. The results of the study are as follows. First, thestudents’ literacy culture is manifested in their reading and writing activities. Readingactivities are done because there are assignments related to the courses (60%) and becausethey like reading (11%). Writing activities done because they like them are in a range of17%-40% and those done because there are demands from the courses are 25-42%. Studentswho link reading and writing activities reach 53%. Second, constraints in literacy culturecome from the students and the environment. The former are in general due to laziness,lack of motivation, not being focused, fatigue and boredom, no writing ideas, difficulty incomposing words and sentences, and confusion, while the latter include, among others,lack of reference in the library and references in foreign languages.Keywords: literacy culture, reading and writing activities